2017
DOI: 10.1111/1365-2664.12917
|View full text |Cite
|
Sign up to set email alerts
|

A three decade assessment of climate‐associated changes in forest composition across the north‐eastern USA

Abstract: 1. Climate-associated changes in forest composition have been widely reported, particularly where changes in abiotic conditions have resulted in high mortality of sensitive species and have disproportionately favoured certain species better adapted to these newer conditions. In the north-eastern USA and south-eastern Canada, few studies have examined climate-related influences associated with forest composition, and none have considered broad-scale changes over a long temporal (>25 years) period. 2. We used US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 50 publications
0
19
1
Order By: Relevance
“…On the contrary, support for climate change variables mostly outweighed (based on absolute Wald z value) disturbance ones. South of our study area into the United States, climate gradients and their changes were also shown to have impacts on tree range shifts (Bose, Weiskittel, Wagner, & Pauchard, 2017a; Fei et al, ). Interestingly, despite our studying tree species at their northern range limit in eastern North America, greater extension of the growing season did not always lead to a higher probability of sapling recruitment at a site.…”
Section: Discussionmentioning
confidence: 98%
“…On the contrary, support for climate change variables mostly outweighed (based on absolute Wald z value) disturbance ones. South of our study area into the United States, climate gradients and their changes were also shown to have impacts on tree range shifts (Bose, Weiskittel, Wagner, & Pauchard, 2017a; Fei et al, ). Interestingly, despite our studying tree species at their northern range limit in eastern North America, greater extension of the growing season did not always lead to a higher probability of sapling recruitment at a site.…”
Section: Discussionmentioning
confidence: 98%
“…, Bose et al. , SLU ) and is often accelerated by climate‐change induced increase in forest productivity (Gauthier et al. , Gonsamo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Forest density is increasing in many northern forest regions (Rautiainen et al 2011, Bose et al 2017, SLU 2017 and is often accelerated by climate-change induced increase in forest productivity (Gauthier et al 2015, Gonsamo et al 2017. Projected increase in productivity under climate warming may also allow further expansion of industrial forestry operations into areas where productivity is currently too low (Raunikar et al 2010).…”
Section: The Future Of Northern Forests?mentioning
confidence: 99%
“…Also, black spruce benefits more from large fires, owing to its aerial seed bank that persists in serotinous cones remaining in the canopy for many years, until a fire opens them to liberate seeds. If climate change progresses toward warmer conditions with no evidence of dryness (Bose, Weiskittel, & Wagner, ), large fires would be expected to be less frequent, to be replaced with small fires. Also, higher predicted temperatures are expected to stimulate seed supplies (van der Meer, Jorritsma, & Kramer, ; Messaoud, Bergeron, & Asselin, ; Roland, Schmidt, & Johnstone, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fir expansion would occur through higher seed inputs in the vicinity of balsam fir stands in the coniferous domain. To be effective, balsam fir invasion following small fires would be preceded by its establishment on suitable sites (Bose et al, ). Therefore, the dependence of regeneration on parental trees and site condition, as has been illustrated by the current research, would help to better address real effects of climate change and disturbance on vegetation composition and dynamics in the boreal forest.…”
Section: Discussionmentioning
confidence: 99%